2016
DOI: 10.1016/j.biotechadv.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells and injectable hydrogels: Synergistic therapeutics in myocardial repair

Abstract: One of the major problems in the treatment of cardiovascular diseases is the inability of myocardium to self-regenerate. Current therapies are unable to restore the heart's function after myocardial infarction. Myocardial tissue engineering is potentially a key approach to regenerate damaged heart muscle. Myocardial patches are applied surgically, whereas injectable hydrogels provide effective minimally invasive approaches to recover functional myocardium. These hydrogels are easily administered and can be eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
102
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 201 publications
(300 reference statements)
1
102
0
Order By: Relevance
“…However, the selection on the modulus of the hydrogel systems from MPa to Pa level is significantly different in various research reports. It is a general belief that hydrogels should possess mechanical properties comparable to that of the native myocardium to provide adequate mechanical support to the infarcted myocardium [5]. However, in our latest research, we found that injectable biomaterials in vitro applications can have a very low stiffness (25 Pa), and a significant improvement of heart functions (ejection fraction and infarction size) was achieved, which is comparable to the other reports with much stiffer hydrogels.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…However, the selection on the modulus of the hydrogel systems from MPa to Pa level is significantly different in various research reports. It is a general belief that hydrogels should possess mechanical properties comparable to that of the native myocardium to provide adequate mechanical support to the infarcted myocardium [5]. However, in our latest research, we found that injectable biomaterials in vitro applications can have a very low stiffness (25 Pa), and a significant improvement of heart functions (ejection fraction and infarction size) was achieved, which is comparable to the other reports with much stiffer hydrogels.…”
supporting
confidence: 81%
“…A longer remaining period may hinder repair process. It should be noted that there is still much debate as to the mechanical and degradation properties of injectable materials applied for MI, due to the large disparity between different research reports [2,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The transposition of a fat flap over the ischemic myocardium has recently been proposed, with promising results in the swine preclinical model of MI [82]. Tissue-engineered, hydrogel-based Mesenchymal stem cells (MSCs) [83] and endothelial progenitor cell [84] therapy have been shown some promising results in re-vascularizing the ischemic myocardium and preserving ventricular function through paracrine effects [85]. Table 3 presents recent cell based clinical trials for cell based therapies of regeneration of myocardium.…”
Section: Regeneration Of Myocardiummentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] By modulating the chemical or physical interactions between natural and/or synthetic polymeric materials, various types of hydrogels have been developed. [10][11][12][13][14][15] Although the chemical gelation strategy using synthetic polymers shows advantages, such as the systematic control of molecular structure and resultant hydrogel properties, toxicity issues still limit their wide adoption in clinical fields.…”
Section: Introductionmentioning
confidence: 99%